Mortalidad materna en Hospital de apoyo I – integrado – IPSS Juanjui 1988 - 1992 - Chávez Flores, Maribel (1993)
In developing countries among which is our country, maternal mortality is high compared to industrialized countries where it is observed that infection, bleeding and Abortion are less frequent (4). We know that the causes of maternal mortality vary depending on the degree of development of each social group, the quality of care that is provided to mothers, health system structure and reference for each study population (4) (14). In underdeveloped countries like ours information on maternal death does not accurately reflect the magnitude of the problem by the high percentage of emission in the statistical record, also because few studies of national dimension, information is generally taken from local studies that reflect different realities within each country, usually with higher rates of maternal mortality in rural and less social development regions (4). Maternal mortality occurred in a hospital in a particular region or country is a fact Priceless value, because their study enables us to evaluate the quality of existing services Obstetricians and also value the degree of health education of the population who demand these services. (11) (20). Maternal death is the death of the wife for any cause during pregnancy until 42 days after termination of pregnancy, regardless of the age of the pregnancy at the time of the determination or the method by which the it was determined (4), (14), (17). The high maternal mortality primarily affects countries underdeveloped in which per 100, 000 live births, 550 women die. These rates are 50 to 100 times higher in: underdeveloped countries than those reported in developed countries such as Sweden, England, USA. US, Japan whose numbers range between 3.8 and 45 per 100,000 live births {13). Due to the economic crisis facing our country health programs to prevent or reduce the incidence of diseases or maternal complications, the health status of this population remains unsatisfactory at high risk of becoming ill or dying, this affects mainly the maternal and child population (6). So, in 1980 the national maternal mortality rate was 32.0 per 10,000 N .V., Almost similar to 1987 was 30.3 per 10,000 births A recent study of Cervantes (4) reveals an average of 16.5 x 10,000 nv (1) Hospitals in Peru. Maternity of Lima in the penultimate year period (1980-1984) had a maternal mortality rate of 9.3x10,000 n. v. (11). The Hospital Cayetano Heredia in Lima between (1975-1984) Maradiegue (10) reported a rate of 28.56x10,000 nv And the Teaching Hospital of Trujillo (1964-1984) Caffo reports (3) 20.26xl0,000n.v rate. Then the Mercedes Teaching Hospital of Chiclayo (1981-1990) Heredia (6) present a maternal mortality rate of 15.5xl0, 000n.v. Support Hospital of Chimbote Eleazar Guzman Barron (1982-1989) Wong (20) reported a rate of 16.0xl0,000 nv These differences are estimated which are closely related to the economic, cultural and social health of a region state. However Honorio Delgado Hospital of Arequipa in a study between the years of 1966-1984 Linares (7) reported in the first year rate 22.3x10,000 nv and last year 16.0xl0, 000 n.v. The lea Regional Hospital had 29 maternal deaths between (1967-1981) that 11.6x10,000 nv. The Hospital represents the Cuzco rate was 161 deaths (1964-1984) Linares (7) reported a rate of 3 38.6xl0 , 000 nv and Victor Lazarte Echegaray IPSS Trujillo, Urbina (18) Hospital reported between (1981-1990) the rate of maternal mortality 2.Sxl0,000 nv this rate is really low you could tell by the factor treated, different realities Socioeconomic conditions in both population and infrastructure conditions As the recent study of Cervantes (4) whose theme was "Mor-Hospital Maternal mortality in Peru reported the lowest highest rate in the Department of San Martin with 90.3x10,000 nv and Ica with 5.5xl0, 000 nv This multiple difference in the rates of maternal mortality apart from their different realities, seems also to social and economic main factors being the lack of qualified staff and adequate delivery units, lack of family planning services, lack of health education deficit in food and hygiene deficiency. As these unfavorable improve social and economic conditions, differences in maternal mortality rates decrease without any doubt.